Construction of Mathematics Cognitive Test Instrument of Computational Thinking Model for Madrasah Aliyah Students - Istiqlal, Muhammad; Istiyono, Edi; Widihastuti, Widihastuti; Sari, Desy Kumala; Danni, Rahmat; Safitri, Islamiani (Nazhruna: Jurnal Pendidikan Islam, 2024)
Mathematical knowledge and computational thinking train students' ability to reason, and this is needed to be able to compete in the digital era in the future. This study aims to construct a mathematical cognitive test instrument using the computational thinking (CT) model that meets the validity, reliability, and good item criteria and provides new insights into how to apply computational thinking in Islamic education (madrasah). This research includes development research consisting of design and implementation stages with a sample of 160 madrasah aliyah students in the Sleman district. Instrument validity was conducted by proving content validity. Reliability was estimated using the separation reliability coefficient, and the quality of the instrument was analyzed using the Rasch model. The instrument was declared reliable (separation reliability coefficient of 0.8059), classified as a good fit for the model, with a p-value of 0.64 > 0.05), and effective in measuring mathematics skills with a percentage of 99.85%. The instrument developed opens the insight that the subject matter in madrasah can be integrated with computational thinking skills and can be used as an alternative for diagnostic, formative, and summative tests.